The Effectiveness of Combining Artificial Intelligence with PhET Simulations to Bridge Fundamental Physics Knowledge Gaps in Science Education for Students - Olfiane Tamarengki; Andita Nur Sakinah Lili Budiarti; Indah Kristiani Siringo Ringo; Rasmita sabtu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of integrating Artificial Intelligence (AI) and PhET simulations in improving the learning outcomes of first-semester students in the Science Education Program at Khairun University. The research employed a quasi-experimental design with a one-group pretest-posttest approach involving 28 students. The research instrument consisted of a learning achievement test, analyzed using a paired sample t-test and normalized gain (N-gain). The findings revealed a significant increase in posttest scores compared to pretest scores (p < 0.05), with an average N-gain categorized as medium. These results indicate that integrating AI and PhET-based learning successfully enhances students’ conceptual understanding, promotes learning autonomy, and bridges the gap in fundamental physics knowledge. The study highlights the importance of employing intelligent technologies and interactive simulations as innovative strategies in 21st-century science education.